How Ready are Pediatricians and Family Physicians in Saudi Arabia to Perform Clinical Screening of Developmental Dysplasia of the Hip? - Suqaty R; Alomran AK; Alkhalifah MK; Aldughaythir SS; Albeshry AM; Aldilaijan Y; Alzahrani MT; Alhussainan T (Journal of Multidisciplinary Healthcare, 2023)
Rayyan Suqaty,1 Ammar K Alomran,2 Mohammed K Alkhalifah,3 Saad S Aldughaythir,4 Abdulrahman M Albeshry,5 Yousif Aldilaijan,6 Mohammed T Alzahrani,1 Thamer Alhussainan1 1Department of Orthopedic Surgery, King Faisal Specialist Hospital & Research Center, Riyadh, Saudi Arabia; 2Department of Orthopedics, College of Medicine, Imam Abdulrahman bin Faisal University, Dammam, Saudi Arabia; 3Department of Family Medicine & Polyclinics King Faisal Specialist Hospital and Research Centre, Riyadh, Saudi Arabia; 4Department of Pediatrics, King Faisal Specialist Hospital and Research Centre, Riyadh, Saudi Arabia; 5Department of Family and Community Medicine, Faculty of Medicine, University of Jeddah, Jeddah, Saudi Arabia; 6Primary Health Care Centers, Eastern Health Cluster, Khobar, Saudi ArabiaCorrespondence: Thamer Alhussainan, Department of Orthopedic Surgery, King Faisal Specialist Hospital & Research Center, Al Mathar Ash Shamali, Riyadh, 11564, Saudi Arabia, Tel +966504181881, Fax +96614414839, Email alhussainan.t@gmail.comBackground: Developmental dysplasia of the hip (DDH) is one of the most common hip pathologies in pediatric age group and late diagnosis remains a major concern in Saudi Arabia.Objective: The aim of this study is to examine the ability of Saudi Arabian pediatricians and family physicians to conduct clinical screening for (DDH) by estimating their clinical knowledge and skills and analyzing the gaps therein to determine whether there is potential to launch a national screening protocol for DDH in Saudi Arabia.Methods: This is a multicenter cross-sectional study from three major regions in Saudi Arabia (Central, Eastern and Western provinces). The assessed aspects are risk factors, age of screening, incidence in Saudi Arabia, physical signs and diagnostic markers, and treatment, along with their ‘clinical knowledge and skills’ score.Results: Half of the participants were pediatricians, while the rest were family physicians. More than a third of the participants were considered to have adequate knowledge, ie, above the mean score. Dimensions with the most significant knowledge gaps included the incidence of DDH in Saudi Arabia, adverse effects of swaddling, and the management of a high-risk infants presenting with a negative physical examination. Additionally, there were relatively low rates of awareness regarding positive risk factors as well as a generally poor ability to identify physical signs. Clinical knowledge and skill levels were significantly lower among family physicians.Conclusion: Pediatricians and family physicians in Saudi Arabia still need further training to improve their clinical skills for DDH screening. The proper administration of training programs could eventually enable the gradual implementation of a national systematic screening program.Keywords: orthopedic, pediatrics, observational study, pediatricians, family physicians, developmental dysplasia of the hip